Blockade of glutamate receptor ameliorates lipopolysaccharide-induced sepsis through regulation of neuropeptides. Issue 3 (8th May 2018) - Zhe, Zhai; Hongyuan, Bi; Wenjuan, Qiao; Peng, Wang; Xiaowei, Liu; Yan, Gao
Abstract : Glutamate receptors (N-methyl-d -aspartate receptor (NMDAR)) are expressed mainly in the central nervous system (CNS), but several potentially important exceptions are worth mentioning. Recently, NMDAR, a glutamate receptor, has been reported to be found in the lungs. NMDAR is activated in acute lung injury (ALI). Here, the present experiment was designed to examine whether NMDAR blockade (MK-801) ameliorates ALI through affecting neuropeptides in LPS-induced sepsis animal models. Male Kunming mice were divided into control group, LPS group, control + MK-801 group, and LPS + MK-801 group. Bronchoalveolar lavage fluid (BALF) was collected and evaluated. The lung histological pathology was assayed by immunocytochemistry staining. Western blot was used to measure PGP9.5, substance P (SP), and vasoactive intestinal polypeptide (VIP). Results showed that LPS-induced mice animal models were ameliorated by co-treatment with the MK-801, an uncompetitive NMDAR antagonist. Moreover, the protective effects of MK-801 attributed to the increased secretion of VIP and decreased secretion of SP. The results of the present study indicated that the blockade of NMDAR may represent a promising therapeutic strategy for the treatment of sepsis-associated ALI through regulation of neuropeptides.